2020
DOI: 10.1096/fj.202002097
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in alpha‐1 antitrypsin deficiency allele frequencies may partially explain national differences in COVID‐19 fatality rates

Abstract: This article was fast-tracked under a recently instituted interim policy in which editors may, at their discretion, accept coronavirus-related manuscripts submitted for the Review, Perspectives, and Hypotheses categories without additional review.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 29 publications
2
46
0
2
Order By: Relevance
“… 7 A significant positive correlation was reported between the combined frequencies of the PI*SZ genotype in 67 countries and their reported COVID‐19 mortality. 8 These observations are intriguing, but interpretations are challenged by many confounding factors (eg, socioeconomic status and ethnicity) and further investigations are required.…”
mentioning
confidence: 99%
“… 7 A significant positive correlation was reported between the combined frequencies of the PI*SZ genotype in 67 countries and their reported COVID‐19 mortality. 8 These observations are intriguing, but interpretations are challenged by many confounding factors (eg, socioeconomic status and ethnicity) and further investigations are required.…”
mentioning
confidence: 99%
“…Moreover, the underlying mechanisms of A1AT on anti-viral, anti-inflammation, anti-cell death, antiproteases, and anti-coagulation should be studied. Furthermore, Shapira et al found a significant positive correlation between the combined frequencies of the A1AT deficiency alleles in 67 countries and their reported COVID-19 mortality rates (Shapira et al, 2020). Given the important role that A1AT plays in the prevention and treatment of the pathological process of SARS-CoV-2 infection, patients with A1AT deficiency may be more susceptible to SARS-CoV-2 viral infection with worse clinical outcomes.…”
Section: Research Agendamentioning
confidence: 99%
“…AAT impedes SARS-CoV2 cellular entry and prevents the main clinical complications of severe COVID-19, such as acute inflammation and acute respiratory failure [41]. Therefore, it could be hypothesized that the geographical distribution of pathogenic variants of AAT protein is to a certain extent linked to differences in COVID-19 epidemiology and severity throughout Europe [42]. Furthermore, a Food and Drug Administration-approved AAT augmentation therapy, used for patients with AATD and emphysema, has potential value in managing SARS-CoV-2 infection and an aberrant immune response.…”
Section: Protease Complexed and Cleaved Forms Of Aatmentioning
confidence: 99%